Field Analysis of Stepwise Effective Thermal Conductivity along a Borehole Heat Exchanger under Artificial Conditions of Groundwater Flow - Yoshitaka Sakata (Hydrology, 2017)
Heat advection caused by groundwater flow can potentially improve the performance of a borehole heat exchanger. However, the required flow velocity is not achieved under most natural conditions. This study focuses on artificial groundwater flow generated by pumping and investigates the associated effect in a lowland area near the Toyohira River alluvial fan, Sapporo, Japan. Thermal response test results are compared under natural and artificial groundwater flow conditions. A pumping well is constructed one meter from the borehole. Temperature profiles are measured in the U-tube during testing, using a pair of optic fiber distributed temperature sensors. The effective thermal conductivity is calculated from the profiles obtained in each 10-m sub-layer; this thermal conductivity is termed the stepwise thermal conductivity. Additionally, the upward flow velocity in the pumping well is measured to estimate the mean groundwater flow velocity at the borehole. The results show that effective thermal conductivity increases at depths less than 50 m, where the pumping creates mean velocities greater than 0.1 m d−1 in each sub-layer (1.5 md−1 on average). Thus, a borehole length of 50 m is more reasonable at the test site for its efficiency in a ground source heat pump system coupled with the pumping well than that used.